Optimization of Steel Storage Rack Column and Its Performance Analysis - J, Suresh Kumar; S, Ramesh (International Research Journal of Multidisciplinary Technovation, 2019)
The main aim of the project is to perform a finite element analysis on steel storage columns. Rack systems for pallet storage are important industrial structures by number and commercial value, yet they have been considered only recently in studies aiming at defining practical design rules for their safe use. These structures are always composed of metal elements. The fabrication of rack structures constitutes, indeed, an important application of cold-formed steel products. The need for continuously loading and unloading the shelves in service has induced designers to avoid bracing elements in the longitudinal direction of the racks. Therefore in many cases, lateral stability in this direction is ensured only by the connections between beam and column and by the constraint offered by the base of the columns. ANSYS used for the model development and analysis presented in this paper. The main requirements for a ?nite element (FE) model of storage rack frames is to have the ?exibility to represent the complex cross-section geometries of the members, and the ability to assign semi-rigid behavior to joints and to take into account the effect of local, distortion and ?exural-torsional buckling in determining the ultimate capacity of the structure and optimization.